Organization of medical care for children in Ukraine (review of literature) - V. V. Trokhymchuk; O. I. Belyaeva; L. M. Unhurian (The State Expert Center of the Ministry of Health of Ukraine, 2017)
The realization of high quality medical measures for protecting children's health remains an important issue at the stage of reforming the domestic medicine. The aim of this work was to study and analyze the system of medical aid for children in Ukraine. The research focused on normative-legal acts regulating the organization of medical aid for children. The research methods are informative, retrospective, historical, logical and analytical. The analysis of normative-legal documents regulating the organization of rendering of medical aid for children established their formality and economic groundlessness. According to January 2017, only 35 documents were included into the Registry of medical technological documents in the direction of «Pediatrics». It means that many children's pathological states are not covered by standardization, what reduces the quality of medical aid. The national programs for the improvement of health status of children remained unrealized due to the lack of funding, ill-coordinated links between program implementers, the lack of effective monitoring of the quality and results of realizing the state programs. The implementation result of IMChI strategy was the reduction of mortality rate in children of different age groups in the pilot regions. In terms of reforming the combined model (model III) is the most effective and acceptable for pediatric care rendering. The population expenses reach nearly half of the total funding of the sector, what demonstrates the inconsistencies between the real state of children's assurance in the health care system of Ukraine and national normative acts. It was determined the necessity of structural reorganization of the system, the optimization of beds number, the increase of medical care funding from state and local budgets, the raising of resource efficiency of health care system and the continued development and implementation of modern protocols (standards) for the treatment of children pathologies.